2015
DOI: 10.1002/app.42467
|View full text |Cite
|
Sign up to set email alerts
|

Use of ionic liquids based on phosphonium salts for preparing biocomposites by in situ polymerization

Abstract: A sodium montmorillonite, Dellite HPS, was modified with ionic liquids based on phosphonium salts, such as octadecyltriphenylphosphonium tetrafluoroborate and octadecyltriphenylphosphonium bromide. Thanks to their high thermal stability, these salts can be used during in situ polymerization, a method that favors the achievement of a good dispersion of the clay. Poly(1,4‐dimethylcyclohexane adipate) (PCHA), was chosen as an example of aliphatic polyester which can be a suitable matrix for new biocomposites with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The polycondensation procedure was described in previous papers [ 11 , 44 , 45 ]. 28.1 g (0.180 mol) of FDCA, 24.6 g (0.324 mol) of PD and 320 mg (1.1 10 −3 mol) of Sb 2 O 3 corresponding to 1 wt % respect to the theoretical final polymer, were charged into a glass reactor (250 mL capacity).…”
Section: Methodsmentioning
confidence: 99%
“…The polycondensation procedure was described in previous papers [ 11 , 44 , 45 ]. 28.1 g (0.180 mol) of FDCA, 24.6 g (0.324 mol) of PD and 320 mg (1.1 10 −3 mol) of Sb 2 O 3 corresponding to 1 wt % respect to the theoretical final polymer, were charged into a glass reactor (250 mL capacity).…”
Section: Methodsmentioning
confidence: 99%
“…Bionanocomposites with 5 wt% loading of the organo-modified LDHs were prepared by in situ polymerization following a common procedure already reported [30]. As an example, the procedure for preparing PBS:Zn 2 Al/VA was as follows: a round-bottomed, wide-neck glass reactor (250-mL capacity) was loaded with BD (29.6 g, 328 mmol), TBT (0.0585 g, 0.172 mmol), and 2.35 g of Zn 2 Al/VA (previously dried overnight at 105 °C), corresponding to 5 wt% with respect to the polymer theoretical yield.…”
Section: Methodsmentioning
confidence: 99%
“…PBSA is a copolymer of PBS containing a potentially biobased comonomer: dimethyladipate. 30 In this work, the molar feed ratio between succinate and adipate is 80/20, because it was reported that this composition guarantees the best balance between biodegradation rate and thermomechanical properties. 23 As compared to PBS, PBSA is more susceptible to biodegradation because of its lower crystallinity and higher flexibility of the polymer chains.…”
Section: Introductionmentioning
confidence: 99%